Aëtiana V (4 vols.) : An Edition of the Reconstructed Text of the Placita with a Commentary and a Collection of Related Texts - Jaap, Mansfeld,; Runia, David, (Philosophia Antiqua ;, 2020)
A new reconstruction and text of the Placita of Aëtius (ca. 50 CE), accompanied by a full commentary and an extensive collection of related texts. This compendium, arguably the most important doxographical text to survive from antiquity, is known through the intensive use made of it by authors in later antiquity and beyond. Covering the entire field of natural philosophy, it has long been mined as a source of information about ancient philosophers and their views. It now receives a thorough analysis as a remarkable work in its own right. This volume is the culmination of a five-volume set of studies on Aëtius (1997-2020): Aëtiana I (ISBN: 9789004105805, 1996), II (Parts 1&2; set ISBN 9789004172067; 2008), III (ISBN 9789004180413; 2009), IV (ISBN: 9789004361454, 2018), and V (Parts 1-4). It uses an innovative methodology to replace the seminal edition of Hermann Diels (1879).